2019
DOI: 10.3390/ijerph16152653
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Monthly Patterns, Weekly Variations, and the Holiday Effect of Outpatient Visits for Type 2 Diabetes Mellitus Patients in China

Abstract: Objective: To explore the seasonal and monthly patterns, weekly variations, and the holiday effect of outpatient visits for type 2 diabetes mellitus patients, as well as the influence of gender, age, and insurance type on variations. Methods: Data were obtained from the Shandong medical insurance database, including all outpatients in 12 cities of Shandong province in China from 2015 to 2017. The seasonal index (St) was calculated in terms of seasons, months, and weeks by the moving average method. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…UEBMI patients had lower diabetes prevalence than IURMI patients. It may be subject to average individual characteristics in different groups (Huang et al., 2019). IURMI patients mainly consisted of rural residents, urban retired, unemployed, students, and children with lower education levels and poor physical conditions, which may increase the prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…UEBMI patients had lower diabetes prevalence than IURMI patients. It may be subject to average individual characteristics in different groups (Huang et al., 2019). IURMI patients mainly consisted of rural residents, urban retired, unemployed, students, and children with lower education levels and poor physical conditions, which may increase the prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that cold temperature could lead to elevating glycosylated hemoglobin levels and acute complications of diabetes (Hou et al., 2017; Huang et al., 2019). Also, the proportion of the secondary and third industry output has often been used in related diabetes research (Couchoud et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the time to be analyzed, the time in the time series can be based on year, season, month, week, and so on. The seasonal index analysis method of the time series data can be adopted to estimate the seasonal indexes of each season, which can be used to analyze the temporal patterns of waterfront vibrancy (season, month, week, holiday, and weekend) [40].…”
Section: Seasonal Index Analysis Methods Of Time Series Datamentioning
confidence: 99%